2014
DOI: 10.1002/ijc.29121
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics, pharmacodynamics and efficacy on pediatric tumors of the glioma radiosensitizer KU60019

Abstract: We have recently reported that glioblastoma (GB)-initiating cells (GIC) with low expression and/or mutation of TP53 and high expression of PI3K ("responder" genetic profile) can be effectively and safely radiosensitized by the ATM inhibitor KU60019. We report here on drug's diffusion and elimination from the animal body and brain, its effects on orthotopic GB and efficacy toward pediatric GIC. Healthy mice were infused by convection enhanced delivery (CED) with KU60019 and the drug kinetics followed by high pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
74
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 49 publications
(82 citation statements)
references
References 15 publications
(53 reference statements)
8
74
0
Order By: Relevance
“…Disappearance of VE822 after NP-VE822 CED was well represented by a biexponential decay: ~45% of the drug was cleared with a half-life of 2 h, and the remainder of the drug was cleared more slowly with a half-life of 8.3 d. These data indicate that we can achieve sustained concentrations of VE822, a potent and selective DNA repair inhibitor, in the brain by CED of NP-VE822. In addition, these findings confirm previous literature findings demonstrating rapid clearance of small molecules from the brain parenchyma (20). …”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Disappearance of VE822 after NP-VE822 CED was well represented by a biexponential decay: ~45% of the drug was cleared with a half-life of 2 h, and the remainder of the drug was cleared more slowly with a half-life of 8.3 d. These data indicate that we can achieve sustained concentrations of VE822, a potent and selective DNA repair inhibitor, in the brain by CED of NP-VE822. In addition, these findings confirm previous literature findings demonstrating rapid clearance of small molecules from the brain parenchyma (20). …”
Section: Resultssupporting
confidence: 91%
“…The use of CED in humans with intracranial tumors has been shown to be safe in both adults and children with gliomas (1719). Although CED provides enhanced drug penetration, most small molecules administered directly to the brain are prone to rapid clearance from the brain parenchyma, which usually leads to undetectable drug levels 24 hours after the end of a course of CED (20). CED typically is only administered once because of the complexity and potential morbidity of the procedure.…”
Section: Introductionmentioning
confidence: 99%
“…This is supported by the reduced therapeutic effect observed when orthotopic tumours are developed using primary GIC rather than established cell lines ( Fig. 1 and [14]). In other words, the profound polymorphic nature of humans and their tumours may damp the therapeutic effects in aggregate studies.…”
Section: Determine the Right Treatment Schedulementioning
confidence: 79%
“…For instance, the observed short-lived clinical benefit of bevacizumab in GB [8,9] may not mean that bevacizumab cannot improve OS of GB patients but rather, that the employed treatment schedule was wrong. In our preclinical studies with ATM inhibitors as GB radiosensitizers, we observed efficacy under a narrow combination of ATM inhibitor concentration and radiation dose [14] and the treatment schedule was profoundly affected by the cell's environment: the same GIC line could be radiosensitized in our preclinical studies with different treatment schedules if grown into a petri dish or orthotopically in a mouse brain, and, most probably the same will happen when tumours will have to be treated in human brains (Fig. 2).…”
Section: Determine the Right Treatment Schedulementioning
confidence: 88%
See 1 more Smart Citation